Business Analysis Fumigation of Pangan Catfish with salai method in Kampar Regency, Riau - Shiffa Febyarandika Shalichaty (JURNAL PERIKANAN DAN KELAUTAN, 2022)
Pangan Catfish is one of the native fish of Indonesian waters. The majority of catfish in Indonesia comes from aquaculture. Pangan Catfish production in 2020 in Kampar Regency reached 32.402.126 tons. Pangan catfish is impossible to be sold in fresh form because there is no market that can accommodate large amounts of fresh fish. The absence of business management in the center of the salai processing requires an analysis of the salai fish processing business. This needs to be done to see the feasibility of the salai fish processing business, especially after being affected by the Covid-19 pandemic. This research was conducted at the pangan catfish Processing Center in Koto Masjid Village, XIII Koto Kampar District, Kampar Regency, Riau Province. Business feasibility analysis used is Net Present Value (NPV), Internal Rate of Return (IRR), B/C Ratio and Payback Period. The businesses that were used as research samples were 8 business units. The amount of fumigasion business income reaches Rp. 17,469,000,000/year with costs that reach Rp. 16,290,804,375/ year. The average profit of fumigasion pangan catfish using the salai method in Kampar Regency is Rp. 1,178,195,625,-/ year or Rp. 98,182,987,-/month. Analysis of the business of fumigasion pangan catfis with the salai method in Kampar Regency has an NPV value of Rp. 5,543,328,918,-, the IRR value is 63%, the IRR value is 1.08 and the Payback period value is 3.27. The business of fumigasion pangan catfis said to be feasible with a return of capital in the medium category.